Posterior parietal cortex and long-term memory: some data from laboratory animals - Myskiw, Jociane C.; Izquierdo, Iván (Frontiers in Integrative Neuroscience, 2012)
The posterior parietal cortex (PPC), long viewed as just involved in the perception of spatial relationships between the body and its surroundings and of movements related to it has in recent years been shown to participate in many other cognitive processes, among which working memory and the consolidation and retrieval of episodic memory. The neurotransmitter and other molecular processes involved have been determined to a degree in rodents. More research will no doubt determine the extent to which these findings can be extrapolated to primates, including humans. In these there appears to be a paradox: imaging studies strongly suggest an important participation of the PPC in episodic memory, whereas lesion studies are much less suggestive, let alone conclusive.